Can Viewing Nature Through Windows Improve Isolated Living? A Pathway Analysis on Chinese Male Prisoners During the COVID-19 Epidemic - Li, Hansen; Zhang, Xing; You, Chengming; Chen, Xin; Cao, Yang; Zhang, Guodong (Frontiers in Psychiatry, 2021)
Nature exposure is known to promote life satisfaction and well-being, and indirect exposure through windows is likely to benefit isolated populations. However, whether such type of exposure can benefit prisoners, the extremely isolated population, is unknown. In the current study, we investigated 326 male prisoners from three prisons in southwest China. Psychological variables including depression, anxiety, loneliness, distress tolerance, life satisfaction, and well-being were measured using the Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder Scale (GAD-7), short-form UCLA Loneliness Scale (ULS-6), Distress Tolerance Scale (DTS), Satisfaction with Life Scale (SWLS), and 5-item World Health Organization Well-Being Index (WHO-5), respectively. Structural equation modeling was employed to identify the pathways from the visibility of nature through windows to prisoners' life satisfaction and well-being. Our results demonstrated that visibility of nature promoted the frequency and duration of viewing nature through windows. The frequency directly affected well-being, but the duration did not effectively affect any measured variables. The visibility of nature enhanced life satisfaction mainly via direct effects but enhanced well-being mainly via indirect effects. Regarding the indirect pathways, the visibility of nature increased distress tolerance and thus reduced loneliness and mental health problems. The reduced mental health problem, in turn, promoted life satisfaction and well-being. Our findings suggest that nature exposure through windows is effective in enhancing prisoners' life satisfaction and well-being. The policymaker may need to consider nature-based solutions such as indirect nature exposure in prions to benefit isolated populations.